Agronomic assessment of a genotypes collection of Melilotus officinalis - Lahkim Bennani M.; Ayadi M.; Aarab A.; Khaddor M. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
This study is aimed to evaluate the agronomic performance of twenty ecotypes of yellow sweet clover which were collected from the North-West of Morocco and were cultivated in the experimental station of Boukhalef (Tangier). The samplings were realized during the vegetative, budding and flowering stages. The results showed that yellow sweet clover have a high production of dry matter. The dry matter yield (DMY), the leaves on steam report (LSR) and the stem’s diameter (SD) depends significantly of the maturation stage and the origin of ecotypes. From the vegetative to the flowering stage, the DMY increased significantly from 6.54 to 10.59 t/ha (P<0.001), from 61.96 cm to 142.36 cm for plant height (P<0.001) and SD from 6.5 to 7.74 mm (P<0.001), while the LSR decreased significantly from 0.82 to 0.61 (P<0.001). Between the ecotypes, DMY, LSR and SD varied significantly from 14.81 t/ha (E34) to 4 t/ha (E3) (P<0.01), 1.18 (E3) and 0.6 (E1 and 9) (P<0.001), from 8.91 (E23) to 6.21 mm (E13) (P<0.01) respectively. The highest values of number of ramifications and foliar area were obtained in the flowering stage with 21.50 and 24.05 mm2, respectively. The agronomic evaluation showed that the yellow sweet clover presents a sure interest as forage species for animals feeding.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)